Integrated microbiome and metabolome analysis reveals that new insight into Radix pseudostellariae polysaccharide enhances PRRSV inactivated vaccine - Xu, Gaolin; You, Zelong; Zheng, Yu; Feng, Qixian; Luo, Shishi; Xu, Lihui; Bao, Songying; Wang, Quanxi (Frontiers in Immunology, 2024)
In this study, we investigated how Radix pseudostellariae polysaccharide (RPP) enhances the immune response of the inactivated porcine reproductive and respiratory syndrome virus (PRRSV) vaccine through interactions with the microbiome and metabolome. We pre-treated sows with 10 mg/kg body weight of RPP via drinking water for seven days prior to intramuscular injection of the PRRSV vaccine. This significantly increased the concentrations of PRRSV GP5 protein antibody, interleukins (IL)-2, IL-4, IL-10, and interferon (IFN)-γ. Oral administration of RPP also significantly improved the abundance of beneficial bacteria in the stool, such as Parabacteroides distasonis and Prevotella copri, Eubacterium_sp., Clostridium_sp._CAG:226 and decreased the levels of potentially pathogenic bacteria, such as Paraeggerthella and [Clostridium] innocuum, compared to the vaccine alone. These bacterial changes were confirmed using quantitative real-time polymerase chain reaction (Q-PCR). Moreover, RPP treatment significantly increased the blood concentrations of Ltheanine, Taurodeoxycholic acid (TDCA), and N-Arachidonoyl Proline, and decreased the levels of L-glutamine, Oclacitinib, Lipoxin C4, and leukotriene C5 in sows after immunization (P<0.05). The concentrations of various blood metabolites were validated using sandwich ELISA, confirming the accuracy of the metabolomics data. Intriguingly, the integration of microbiome and metabolome analyses highlighted the significance of Prevotella_copri and TDCA. We consequently developed a mouse immunity model using GP5 protein and discovered that oral administration of RPP significantly enhanced the levels of GP5 protein antibodies, IL-2, IL-4, IL-10, and IFN-γ in mouse serum. It also increased the number of CD3+ and CD3+CD4+ cells in the spleen. Additionally, Prevotella_copri was administered into the large intestine via the anus for seven days prior to the intramuscular injection of the PRRSV GP5 protein. The results demonstrated a significant increase in TDCA ， GP5 antibody concentration in the mouse serum, indicating that RPP modulates Prevotella_copri to elevate its metabolite TDCA, thereby enhancing the GP5 antibody level.